Abnormal cerebral haemodynamics in perinatally asphyxiated neonates related to outcome. Issue 2 (1st September 1999) - Meek, Judith H; Elwell, Clare E; McCormick, David C; Edwards, A David; Townsend, Janice P; Stewart, Ann L; Wyatt, John S
Abstract : AIM: To measure changes in cerebral haemodynamics during the first 24 hours of life following perinatal asphyxia, and relate them to outcome. METHODS: Cerebral blood volume (CBV), its response (CBVR) to changes in arterial carbon dioxide tension (PaCO2 ), and cerebral blood flow (CBF) were measured using near infrared spectroscopy (NIRS) in 27 term newborn infants with clinical and/or biochemical evidence consistent with perinatal asphyxia. RESULTS: Both CBF and CBV were higher on the first day of life in the infants with adverse outcomes, and a CBV outside the normal range had a sensitivity of 86% for predicting death or disability. The mean (SD) CBVR on the first day of life was 0.13 (0.12) ml/100 g/1/kPa, which, in 71% of infants, was below the lower 95% confidence limit for normal subjects. CONCLUSION: An increase in CBV on the first day of life is a sensitive predictor of adverse outcome. A reduction in CBVR is almost universally seen following asphyxia, but is not significantly correlated with severity of adverse outcome.